Study on the Utilization and Impact of Financial Derivatives in Chinese Listed Companies - Sun Pengpeng (SHS Web of Conferences)
In recent years, Chinese companies have been facing increasing risks in the financial market. In addition, international commodity prices fluctuated dramatically due to the geopolitical and global economic situation, further increasing the business risks of enterprises. Against this background, the importance of financial derivatives as a risk management tool is becoming more and more prominent, and the demand for their application by enterprises is rising. This paper systematically analyses the development status, structure and change trends of the financial derivatives market of Chinese listed companies and discusses how enterprises can optimize risk management and financial decision-making through derivatives. The study finds that the number of listed companies disclosing derivative financial assets grows significantly between 2019 and 2023, and the use of financial derivatives expands gradually, especially in the areas of interest rate, equity and currency derivatives. The findings of this study provide a reference for firms to formulate more effective risk management strategies and empirical support for policy makers to optimize the regulatory system and market structure.